Regulation of mitochondrial Ca(2+) and its effects on energetics and redox balance in normal and failing heart - Liu, Ting (2009)
Ca(2+) has been well accepted as a signal that coordinates changes in cytosolic workload with mitochondrial energy metabolism in cardiomyocytes. During increased work, Ca(2+) is accumulated in mitochondria and stimulates ATP production to match energy supply and demand. The kinetics of mitochondrial Ca(2+) ([Ca(2+)](m)) uptake remains unclear, and we review the debate on this subject in this article. [Ca(2+)](m) has multiple targets in oxidative phosphorylation including the F1/FO ATPase, the adenine nucleotide translocase, and Ca(2+)-sensitive dehydrogenases (CaDH) of the tricarboxylic acid (TCA) cycle. The well established effect of [Ca(2+)](m) is to activate CaDHs of the TCA cycle to increase NADH production. Maintaining NADH level is not only critical to keep a high oxidative phosphorylation rate during increased cardiac work, but is also necessary for the reducing system of the cell to maintain its reactive oxygen species (ROS) — scavenging capacity. Further, we review recent data demonstrating the deleterious effects of elevated Na(+) in cardiac pathology by blunting [Ca(2+)](m) accumulation.